Substance and non-substance addictions - Henriques, S. (2019)
What are we talking about when we speak of substance and nonsubstance addictions? Why is prevention important to society? What are the impacts of prevention on general health? These questions were the guidelines for structuring this paper, in which the conceptualization of prevention and prevention practices are systematically discussed. Furthermore, some emerging challenges in the development of preventive strategies are raised. The present paper starts with a theoretical debate, supported with empirical evidence and literature.